Edukasi Filtrasi Air Rumah Tangga Berbasis Tanaman Genjer sebagai Teknologi Tepat Guna bagi Komunitas PKK - Resta Rene Mondina; Alfia Dewi Fadwati (Keris: Journal of Community Engagement, 2026)
Limited access to safe household water remains a significant environmental issue in many urban and peri-urban communities in Indonesia, particularly in densely populated areas that rely on shallow groundwater. This community engagement program aimed to introduce a household biofiltration system using locally available Limnocharis flava through environmental education and appropriate technology implementation. The program involved 25 members of the Family Welfare Empowerment (PKK) community and employed the Asset-Based Community Development (ABCD) and Community Development (Comdev) approaches through educational sessions, demonstrations, guided practice, and participatory reflection. All participants actively attended the activities and practiced the construction and operation of the household biofiltration system. The introduced technology was positively received because it was considered relevant to local environmental conditions, readily available resources, and household needs. Although the program did not include a quantitative evaluation of knowledge improvement, the implementation demonstrated that nature-based, low-cost biofiltration technology has the potential to support environmentally friendly household water management. Continued mentoring and quantitative evaluation are recommended to assess long-term technology adoption and program effectiveness.